(untitled) (Anwer Khan Modern Medical College Journal, 2017)
Chronic arsenic poisoning is an alarming environmental health problem in Bangladesh. The toxicity of arsenic compounds depends on the amount, chemical and physical form of arsenic and the duration of exposure to arsenic. Skin manifestations are the prime and common manifestations of Arsenicosis. Patients are presenting with various complications relating to chronic arsenicosis, out of them we are reporting 2 cases of squamous cell carcinoma of skin. All were female, married, age ranging from 40-60 years, hailed from endemic zone of arsenicosis and the disease which were confirmed by histopathologically. Anwer Khan Modern Medical College Journal Vol. 7, No. 2: Jul 2016, P 53-55